2019
DOI: 10.1302/2058-5241.4.190022
|View full text |Cite
|
Sign up to set email alerts
|

Robotic technology in total knee arthroplasty: a systematic review

Abstract: Robotic total knee arthroplasty (TKA) improves the accuracy of implant positioning and reduces outliers in achieving the planned limb alignment compared to conventional jig-based TKA. Robotic TKA does not have a learning curve effect for achieving the planned implant positioning. The learning curve for achieving operative times comparable to conventional jig-based TKA is 7–20 robotic TKA cases. Cadaveric studies have shown robotic TKA is associated with reduced iatrogenic injury to the periarticular soft tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
146
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 164 publications
(152 citation statements)
references
References 51 publications
4
146
0
2
Order By: Relevance
“…(e) The joint flexion and extension gap, joint stability, range of motion, and lower limb alignment can be evaluated by the robot system during the surgery. Meantime, surgeons can make real‐time modifications to bone resections, adjust the position of the prosthesis, and fine‐tuning soft tissue release to achieve the satisfied bone coverage, prosthesis position, knee kinematics, and lower limb alignment 1,30 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(e) The joint flexion and extension gap, joint stability, range of motion, and lower limb alignment can be evaluated by the robot system during the surgery. Meantime, surgeons can make real‐time modifications to bone resections, adjust the position of the prosthesis, and fine‐tuning soft tissue release to achieve the satisfied bone coverage, prosthesis position, knee kinematics, and lower limb alignment 1,30 …”
Section: Resultsmentioning
confidence: 99%
“…MAKO robot‐assisted system, a new semiautomatic robot‐assisted system, can use a three‐dimensional (3D) reconstructions of the knee joint based on computed tomographic (CT) scans to create a preoperative plan, monitor the surgical process in real‐time during surgery, and improve the accuracy of prosthesis 1 . However, in most countries and regions, the application of MAKO robot‐assisted arthroplasty is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding clinical outcomes, patients’ satisfaction was increased in RA-TKA group with better early clinical outcomes compared to CM-TKA and no significant differences of ROM were reported between the two groups, in line with what is reported in the current literature. 12 , 13 Previous studies suggested that postoperative ROM and implant stability are influenced from the posterior inclination of the tibial component. 12 , 30 In addition, insufficient knee ROM is usually caused by inappropriate component sizing, a tight extension or flexion gap, component malalignment or malrotation, a lack of rehabilitation and swelling of the periarticular soft tissue.…”
Section: Discussionmentioning
confidence: 99%
“… 11-13 However, trust on robotic-TKA is limited by increased costs and longer operative time, associated with a lack of long-term evidence comparing clinical and functional outcomes to conventional manual TKA. 13 The restoration of mechanical axis (0° within ± 3° of standard deviation [SD]) through tibial and femoral perpendicular cuts with respect to their mechanical axis is strongly associated with higher implant survivorship and clinical outcomes. 11 , 12 , 14 , 15 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation